Dental manifestation and management of hypophosphatasia - Rena Okawa; Kazuhiko Nakano (Elsevier, 2022)
Hypophosphatasia is an inherited metabolic disorder characterized by defective mineralization of bones and teeth with a wide variety of manifestations, ranging from stillbirth to dental symptoms alone. Recently, the prognosis of severe hypophosphatasia patients has been greatly improved by the introduction of enzyme replacement therapy. The typical dental manifestation is early exfoliation of primary teeth due to disturbed cementum formation, so dentures are recommended to ensure that important oral functions are acquired. Some studies have shown that enzyme replacement therapy improves dental mineralization, resulting in the stabilization of periodontal tissues and better growth of tooth roots. A nationwide Japanese survey revealed the common genetic and dental manifestations of patients with mild hypophosphatasia, which markedly differ from those of the severe forms. There may be many undiagnosed mild patients, so dentists should contribute to the early diagnosis by screening possible cases based on the typical finding of early exfoliation of primary teeth. Early diagnosis is important for patients to receive early intervention in both medical and dental fields. The establishment of fundamental dental therapy to solve the dental problems is still underway and is eagerly anticipated.